Analisis Cerpen “Langit Makin Mendung” Karya Ki Panjikusman dengan Pendekatan Religius - Azizah, Azraril; Abdurrahman, Abdurrahman (Lembaga Yasin AlSys, 2026)
Studies on religiosity in Indonesian literature are abundant; however, research that specifically examines the integration of religious symbolism, social critique, and moral messages in the short story Langit Makin Mendung remains limited. This study aims to analyze the religious values, forms of socio-religious critique, and moral messages conveyed by Ki Panjikusmin through a religious literary approach. The research employs a qualitative method with a descriptive design and applies content analysis techniques to the text of the short story. Data were collected through close reading, identification of symbols, characters, and conflicts, and were then interpreted with reference to theories of religious literature. The findings indicate that the short story mobilizes religious symbols, angelic figures, and satirical events to highlight the erosion of faith, abuse of power, and social hypocrisy in society. These results contribute to strengthening theoretical discussions in religious literary studies and deepen the understanding of the relationship between spirituality and social critique in modern Indonesian literature. The study concludes that faith, honesty, and moral responsibility constitute essential foundations for improving religious life and demonstrates the potential of literary works as media for spiritual and moral reflection. The implications include theoretical contributions to the development of religious literary studies and practical benefits for educators and researchers in using literary texts to foster religious and ethical awareness, while also opening avenues for further exploration of religious meaning-making in other satirical literary texts.